2015
DOI: 10.2337/dc15-0187
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment of Individualized Glycemic Goals in Patients With Type 2 Diabetes: Formulation of an Algorithm Based on a Survey Among Leading Worldwide Diabetologists

Abstract: OBJECTIVEObservations over the past few years have demonstrated the need to adjust glycemic targets based on parameters pertaining to individual patient characteristics and comorbidities. However, the weight and value given to each parameter will clearly vary depending on the experience of the provider, the characteristics of the patient, and the specific clinical situation.RESEARCH DESIGN AND METHODSTo determine if there is current consensus on a global level with regard to identifying these parameters and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 12 publications
0
48
0
1
Order By: Relevance
“…In the recent trend toward individualization of diabetes care, hypoglycemia has been considered as a major barrier to optimal glucose control (which helps in preventing diabetes complications). One recent survey among global opinion leaders in diabetes showed that “the risk of hypoglycemia from treatment” and “the risk associated with hypoglycemia” were important factors that should be considered when setting patients’ glycemic targets [2]. Severe hypoglycemia is defined as an episode of hypoglycemia in which a person’s blood glucose levels become extremely low, requiring the assistance of another person for treatment [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent trend toward individualization of diabetes care, hypoglycemia has been considered as a major barrier to optimal glucose control (which helps in preventing diabetes complications). One recent survey among global opinion leaders in diabetes showed that “the risk of hypoglycemia from treatment” and “the risk associated with hypoglycemia” were important factors that should be considered when setting patients’ glycemic targets [2]. Severe hypoglycemia is defined as an episode of hypoglycemia in which a person’s blood glucose levels become extremely low, requiring the assistance of another person for treatment [3].…”
Section: Introductionmentioning
confidence: 99%
“…The lower HbA1c in these participants may either represent their propensity for developing hypoglycaemia, which leads to lower than average glucose levels, or may indicate an attempt to intensify glucose control, which can possibly lead to recurrent hypoglycaemic events. The glycaemic target of vulnerable participants must be carefully considered, when intensifying treatment with agents that might cause hypoglycaemia and a more lenient HbA1c target may therefore be considered appropriate in these patients …”
Section: Discussionmentioning
confidence: 99%
“…In a recent scenario-based survey evaluating endocrinologists’ perspectives on individualized glycemic target goals based on clinical factors, wide variation existed, with many choosing HbA 1c targets both lower and greater than 8% (64 mmol/mol), even in patients with significant comorbid conditions (32). In addition, individual patient preferences differ.…”
Section: Discussionmentioning
confidence: 99%